Efeito protetor da lectina de sementes de Moringa oleifera na pancreatite aguda induzida por ceruleína em camundongos via modulação da inflamação e estresse oxidativo - Luz, Patrícia Bastos (2017)
Acute pancreatitis (AP) is an inflammatory disease that primarily affects the pancreas, and can progress with insufficiency of many organs, such as lung and liver. Despite its significant morbidity and mortality rate, there are not therapeutic alternatives for PA cure. Moringa oleifera is a plant native to Asia, Africa and South America, with extensive expansion into the Brazilian Northeast and widely used in folk medicine. MoCBP4 is a lectin purified from M. oleifera seeds with anti-inflammatory and antinociceptive activities. The present study aimed to evaluated the effect of MoCBP4 on the functional, inflammatory and molecular alterations characteristic of PA in vivo and in vitro models. Mice were treated orally with MoCBP4 at doses 20, 40 and 80 mg/kg and after 1 hour they received five injections of cerulein (50 μg/kg) intraperitoneally at 1hour intervals between administrations.The animals were euthanized after 6 hours of the last administration of cerulein. The pancreas, lung, liver and blood were collected to evaluate the pancreatic edema, amylase, lipase, AST, ALT, MPO activity, TNF-α, IL-1β, IL-6, NP-SH, MDA, NO2-, COX-2, NF-ĸB and NOSi, in addition to histological analysis. Cytosolic Ca2+ levels were measured in acinar cells stimulated by cholecystokinin-8 (CCK). The effects of MoCBP4 were evaluated on TLC-S-induced acinar cell necrosis and on FMLP and PMA-stimulated neutrophils production of ROS.The statistical analyses were performed using analysis of variance followed by the Newman-Keuls or Kruskal Wallis/Dunn post hoc test. Values of p< 0.05 were considered statistically significant. MoCBP4 (20, 40 and 80 mg / kg) reduced, respectively, pancreatic edema (13%, 21% and 41%); amylase (18%, 14% and 28%); lipase (51%, 39% and 33%); AST (42%, 47% and 36%); ALT (30%, 50%, 37%); MPO activity in the pancreas (58%, 51% and 43%), lung (42%, 56% and 42%) and liver (51%, 66% and 56%). In the histological analysis, MoCBP4 at dose of 40mg / kg was able to significantly attenuate the inflammatory infiltrate and necrosis in the pancreas, besides reducing lung and hepatic damage. MoCBP4 (40 mg/kg) decreased the pancreatic levels of TNF-α, IL1-β and IL-6 (40%, 55% and 67%) and also reduced plasma levels of TNF-α and IL1-β (68% and 63%); MoCBP4 (40 mg/kg) increased plasma levels of NP-SH and significantly reduced MDA and NO2-. MoCBP4 (40 mg / kg) reduced the pancreatic immunostaining of COX-2, TNF-α, iNOS and NF-ĸB.MoCBP4 at concentration 1 μM reduced sustained levels of cytosolic Ca2+ on the acinar cells stimulated by CCK . MoCBP4 (1 μM) attenuated TLC-S-induced acinar cell necrosis in 73%. MoCBP4 (10 μM) attenuated ROS production by neutrophils stimulated by fMLP (59%) and PMA (58%). These data show that MoCBP4 protects against acute edematous pancreatitis induced by cerulein, and this effect is associated with attenuation of local and systemic inflammatory response mediated by reduction of neutrophils and pro-inflammatory cytokines, as well as oxidative stress and tissue injury.In isolated cells, MoCBP4 was able to attenuate neutrophil activation, in addition to reducing overall and sustained of Ca2+ in the acinar cell cytosol and, probably for this reason, reduced cell death by necrosis.